Diagnostic Assessment in Differentiated Learning: Supporting Learners' Needs for Improved Learning Achievement - Amy Siti Nazilah (Research Journal on Teacher Professional Development, 2024)
Differentiated learning have become major focuses in efforts to create a more equitable and inclusive educational system. Diagnostic assessment plays a key role in understanding the individual learning needs of students and designing appropriate interventions. However, the implementation of diagnostic assessment in supporting differentiated instruction still faces challenges. This study aims to explore effective strategies in diagnostic assessment and their impact on the learning process and student outcomes. Findings indicate that implementing differentiated instruction using data from diagnostic assessments positively impacts learning and student outcomes. By understanding students' conditions through diagnostic assessment, teachers can determine appropriate follow-up actions in the form of content, process, or product differentiation. The scholarly contribution of this research lies in a deeper understanding of the role of diagnostic assessment in supporting differentiated instruction. However, further studies are needed to broaden the scope of research and analyze the impact of diagnostic assessment implementation in more depth.